If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -6) + -2x = 9x + 4 Reorder the terms: 3(-6 + x) + -2x = 9x + 4 (-6 * 3 + x * 3) + -2x = 9x + 4 (-18 + 3x) + -2x = 9x + 4 Combine like terms: 3x + -2x = 1x -18 + 1x = 9x + 4 Reorder the terms: -18 + 1x = 4 + 9x Solving -18 + 1x = 4 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -18 + 1x + -9x = 4 + 9x + -9x Combine like terms: 1x + -9x = -8x -18 + -8x = 4 + 9x + -9x Combine like terms: 9x + -9x = 0 -18 + -8x = 4 + 0 -18 + -8x = 4 Add '18' to each side of the equation. -18 + 18 + -8x = 4 + 18 Combine like terms: -18 + 18 = 0 0 + -8x = 4 + 18 -8x = 4 + 18 Combine like terms: 4 + 18 = 22 -8x = 22 Divide each side by '-8'. x = -2.75 Simplifying x = -2.75
| -9-6x=1x-3 | | -19-1/2x=1/6-1 | | -1=-14v+14v | | (5m^3+2m-m)+(m^2+4m-2)=0 | | 36x^5+16x=-52x^3 | | 64v^2=23 | | .2x-2=.4x+4 | | y^2+40y+c= | | (6x^2+4y^2)+(5x^2-3y^2)=x^2+y^2 | | (6x^2+4y^2)+(5x^2-3y^2)=6y | | 6x-9=23 | | 3xsquared=75 | | 7-4/53/5 | | -7(2-8m)=-294 | | 6-9-(3)=0 | | (7/a)=(3/5) | | (y-10)(y^2+10y+4)= | | 4p+4q=48 | | -5a+5+8a=14-24 | | -7(n+4)=-84 | | 4x+3y=235 | | 5x^2+18x-7=0 | | -(n+4)=-84 | | b^4+2b^2-15=0 | | b^4+2b^2+15=0 | | C=T+S+H | | b^2+2b^2+15=0 | | x^2-8x+18x=16 | | 15x^2+13x^2=0 | | 2x-10=2x-10 | | -5x+4+x=4 | | 2x+12+4x=90 |